La propagande arabe anglaise vers le Maghreb pendant la Seconde Guerre mondiale (1939-1943) - Fayçal Cherif (Revue LISA)
In the context of Second World War and its impact in North Africa, propaganda destined for Arab populations takes multiform aspects: radio, newspapers, leaflets, etc.. The propaganda conducted by Great Britain through the BBC, making use of the Arabic language, began in 1939. Programmes from Radio London were in fact an answer to German radio propaganda which had great success in North Africa. During the brief war operations in Morocco, Algeria and Tunisia, from 8 November 1942 to 13 May 1943, this propaganda tried to show and to improve the image of different combatants and to convince Arabs of the justice of their cause. A weekly newspaper published by Great Britain, “Akhbar al Ousbou” (or Weekly Information), was exclusively reserved for the governmental authorities. During the North Africa campaign (Torch), the Royal Air Force dropped leaflets in Arabic, trying to explain their war aims and to secure the support of the population. This article examines the developing of British Arabic propaganda and seeks to measure its degree of success or failure in the face of other subversive propaganda particularly from Germany and Italy and especially its impacts on the North African populations from 1939 till May 1943.